KINERJA SATUAN RESERSE NARKOBA POLRESTA PEKANBARU DALAM PEMBERANTASAN NARKOBA DI KALANGAN PELAJAR DAN MAHASISWA - Sari, Vira Mayang; ", Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The distribution of drug abuse is at an alarming level. In Pekanbaru City itself, drug abusers not only as consumers but also as transit of drug. In addition, drug is not used by businessmen and older people only, but has become a prima donna among the younger generation such as students that potentially the occurrence of lost generation. As a state of qpparatus which of maintaining security and public order, guard, protector and servant to the community of Pekanbaru City. Police Resort with its Unit Anti Drug is required to be able to improve its performance in eradicate drugs in Pekanbaru Police area. This research examines how the performance of the organization of Pekanbaru Police Anti Drug Unit and analyze the factors that influenced both internal and external problem, so as to achieve better performance. This research uses qualitative descriptive type, that is problem solving procedure by exposing data, then analyzed and interpreted by giving conclusion. The collection of data using interviews, observations, and literature study that aims to describe (descriptive) and explain (explanatory or confirmatory) the phenomenon that occurs. Based on the research, the result shows that the performance of Police Anti Drug Unit of Pekanbaru in eradicating of drugs among students in general has been well realized, but not really optimal due to the lack of initiative to conduct coaching and counseling (preventive) of this organization itself. In general, the performance of this organization has been able to perform its duties and functions well, and certainly not apart from the ability of the organization to recognize the needs of the community responses (responsiveness), able to explain in every implementation of the duties that are charged to each unit (responsibility), and the organization is also able to have consistency in performing the duties that are charged (accountability). Factors that influence the performance of Police Anti Drug Unit Pekanbaru in Eradicating of Drug among students is human resources, budget, infrastructure, and community participation. Of the four factors that most dominantly affect to the performance of the organization is the factor of community participation. Keywords: Organizational Performance, Eradication, Drug Abuse.